1971
DOI: 10.1111/j.1467-6494.1971.tb00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Cue utilization and attributional judgments for success and failure

Abstract: Summary Two experiments are reported which examine causal attributions in achievement‐related contexts Subjects were provided with information about an achievement‐related activity (the immediate outcome of the action, percentage of prior success and failure at the same and similar tasks, percentage of success and failure of others, time spent at the task, task structure, and whether the achievement activity was undertaken by oneself or others) The subjects were required to attribute the immediate performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
151
1
5

Year Published

1977
1977
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(173 citation statements)
references
References 7 publications
16
151
1
5
Order By: Relevance
“…This approach may help to clarify the reason that unexpected outcomes in achievement situations are attributed to unstable causes, such as effort or luck, while expected outcomes are attributed to stable causes, such as skill and task difficulty (Frieze & Weiner, 1971). Because unstable causal factors vary over time and across situations, one cannot have prior information about them.…”
Section: Discussionmentioning
confidence: 99%
“…This approach may help to clarify the reason that unexpected outcomes in achievement situations are attributed to unstable causes, such as effort or luck, while expected outcomes are attributed to stable causes, such as skill and task difficulty (Frieze & Weiner, 1971). Because unstable causal factors vary over time and across situations, one cannot have prior information about them.…”
Section: Discussionmentioning
confidence: 99%
“…As may be seen in Table 1, ability was rated comparatively higher in high-status success and in low-status failure than in highstatus failure and low-status success. On the other hand, high-status failure and, particularly, low-status success were attributed to luck more than high-status success and low-status failure (see also, for instance, Deaux & Emswiller, 1974;Frieze & Weiner, 1971). …”
Section: Causal Attribution Scalementioning
confidence: 99%
“…Research in communication began to suggest that adding scarcity to a communication intensifies the evaluative response to that communication even when the response is negative (Bozzolo and Brock 1992;Ditto and Jemmott 1989;Frieze and Weiner 1971). In order to reconcile these opposing effects of scarcity on value, Brock and Brannon (1992) liberalized commodity theory, extending its scope to messages, experiences, traits and skills, and negative objects, granting that commodifying factors polarize evaluative responses.…”
Section: Introductionmentioning
confidence: 99%
“…It subsequently became clear that scarcity does not only affect the value of desirable things. Research demonstrated that, rather than simply enhancing value, scarcity can intensify evaluative responses for negative events as well in contexts like person attribution (Frieze and Weiner 1971), intimate self-disclosure (Petty and Mirels 1981), reaction to medical diagnoses (Ditto and Jemmott 1989), and persuasive communication (Bozzolo and Brock 1992). In a special issue concerned with such intensification effects of scarcity, several possible underlying mechanisms were proposed (Pratkanis and Farquhar 1992), including increased attention (Bozzolo and Brock 1992;Brock and Brannon 1992;Folger 1992).…”
Section: Introductionmentioning
confidence: 99%